2022
DOI: 10.1029/2021jb022621
|View full text |Cite
|
Sign up to set email alerts
|

Aseismic Fault Slip During a Shallow Normal‐Faulting Seismic Swarm Constrained Using a Physically Informed Geodetic Inversion Method

Abstract: How fault slip nucleates, grows, and eventually accelerates is a critical question to describe the driving mechanisms behind earthquakes and faulting phenomena. Our current understanding is consistent but cannot distinguish among various viable mechanisms to explain how fault slip initiates: dynamic triggering (Gomberg &

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 127 publications
(203 reference statements)
0
8
0
Order By: Relevance
“…The closest case is reported by Jiang et al. (2022) in the 2011 Hawthorne seismic swarm, where a significant aseismic slip drives a seismic swarm, leading to an M4.6 mainshock. It may be interesting to perform large‐scale statistics on the candidate pre‐slip clusters like that preceding f 1 in our study. Multiple mechanisms can coexist in a foreshock‐mainshock sequence.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The closest case is reported by Jiang et al. (2022) in the 2011 Hawthorne seismic swarm, where a significant aseismic slip drives a seismic swarm, leading to an M4.6 mainshock. It may be interesting to perform large‐scale statistics on the candidate pre‐slip clusters like that preceding f 1 in our study. Multiple mechanisms can coexist in a foreshock‐mainshock sequence.…”
Section: Resultsmentioning
confidence: 60%
“…Though Tape et al (2018) report possible nucleation signals in the strike-slip fault system in central Alaska, it comes in the form of very low frequency earthquakes, instead of significant foreshocks. The closest case is reported by Jiang et al (2022) in the 2011 Hawthorne seismic swarm, where a significant aseismic slip drives a seismic swarm, leading to an M4.6 mainshock. It may be interesting to perform large-scale statistics on the candidate pre-slip clusters like that preceding f1 in our study.…”
Section: Implications On Foreshock Triggering Modelsmentioning
confidence: 78%
“…There have been accumulated reports on crustal deformations during earthquake swarms (Gualandi et al., 2017; Himematsu & Furuya, 2015; Jiang et al., 2022; Lohman & McGuire, 2007; Martínez‐Garzón et al., 2021; Ruhl et al., 2016; Sirorattanakul et al., 2022; Takada & Furuya, 2010; Wei et al., 2015; Wicks et al., 2011; Yukutake et al., 2022). Previous studies have reported cases where the contribution of aseismic slip in moment release is more than that of seismicity (Himematsu & Furuya, 2015; Lohman & McGuire, 2007; Nishimura et al., 2022; Wicks et al., 2011; Wei et al., 2015; Yukutake et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The seismicity evolution during a swarm is often thought to be governed by external aseismic processes such as a slow slip event, fluid flow, magma intrusion, or a combination. Transient aseismic fault slip in the form of a slow slip event can increase shear stress on neighboring fault patches and has in particular been associated with swarms along oceanic transform faults (e.g., Roland & McGuire, 2009) and extensional or transtensional continental fault systems (e.g., Gualandi et al., 2017; Jiang et al., 2022; Lohman & McGuire, 2007; Martínez‐Garzón et al., 2021; Passarelli et al., 2015). Alternatively, elevated pore pressure from fluid flow or magmatic intrusion can decrease effective normal stress, thus reducing fault strength and bringing the faults closer to failure (e.g., Dieterich et al., 2000; Hubbert & Rubey, 1959; Nur & Booker, 1972).…”
Section: Introductionmentioning
confidence: 99%